Determinants of investment decisions by interest investment as an intervening variable - Saputra, Era Trianita; Susanti, Ari; Octavia, Dewi Ika; Rianto, Rahmad Isa (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2024)
Investment decisions are choices chosen to generate future profits by combining various strategies, opportunities and challenges. The aim of this research is to examine the influence of financial culture, income level through investment interest as variables affecting the investment decisions of residents of the city of Surakarta. The population concerned by this research is made up of residents of the city of Surakarta who wish to invest. The sampling method used structural equation modeling (SEM) analysis to obtain a research sample of 105 samples. The analysis and hypothesis testing method uses the SmartPLS 3.0 analysis method. This research uses quantitative, cross-sectional data with a Likert scale. Research results show that financial literacy influences investment decisions, income level influences investment decisions, financial literacy influences investment interest, income level influences investment interest , investment interest influences investment decisions, financial literacy influences investment decisions by investment interest, income level influences investment decisions by investment interest.